(untitled) (Contemporary Journal of Social Science Review, 2025)
The rapid evolution of digital education has led to the emergence of Smart Learning Environments (SLEs), which integrate advanced technological tools, adaptive learning systems, and AI-driven personalization to enhance educational experiences. However, despite their potential, the effectiveness of SLEs in fostering student engagement and interaction remains a critical concern, particularly in the context of Pakistani higher education. This qualitative study explored the challenges and opportunities associated with SLEs in universities across Lahore, focusing on digital accessibility, engagement barriers, and pedagogical effectiveness. Using a phenomenological research design, semi-structured interviews were conducted with 20 faculty members and 40 students from various universities, offering rich insights into their lived experiences with smart learning technologies. Thematic analysis revealed three primary themes: (1) Digital Divide and Accessibility Issues, (2) Student Engagement and Active Learning, and (3) Faculty Readiness and Digital Pedagogy. Findings indicated that while SLEs enhance flexibility and accessibility, disparities in technological resources, lack of faculty preparedness, and passive learning behaviors hinder their effectiveness. This study highlights the need for policy reforms, faculty training initiatives, and a balanced approach between synchronous and asynchronous learning to optimize the use of SLEs in Pakistani universities. The research contributes to the ongoing discourse on digital transformation in education by providing a context-specific understanding of engagement challenges in SLEs and suggesting practical strategies for improvement.